Pre-operative Assessment of Unexpected Micronutrients Status among Elderly Patients with Elective General Surgery and no Apparent Clinical Indication; Zinc, Magnesium, Calcium, Inorganic Phosphorous - Agin, Kh; Ardehali, SH (International Journal of Medical Toxicology and Forensic Medicine, 2014)
<!–[if gte mso 9]> 800x600 <![endif]–> <!–[if gte mso 9]> 800x600 <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Background: Electrolytes and micronutrients abnormality level can influence the outcome of surgery. Measurement of Zinc (Zn), Magnesium (Mg), inorganic Phosphorous (P) and Calcium (Ca) routinely was not evaluated Pre-operatively. Determinations of serum level of micronutrients are exclusively attended on the emergency conditions or special procedures and rarely applied as pre-operative screening tests among elderly. In addition, older age encounters as an important risk factor due to reduced physiologic reserve, malnutrition and underlying disorders. The aim of the study assessed pre-operatively unexpected serum micronutrients among elderly patients for elective general surgery with no apparent clinical indication. Methods: Our target population is elderly patients from both genders (males and females). Patients that were coming in chest clinic for elective general surgery consultation were enrolled. Zn, Ca, P and Mg levels were measured in serum according to manufacturer’s documentation kits. Results: A total of 171 elderly patients were female 55% male 45%. Mean age was 69.12±6.66 SD years. The frequency of micro-nutrition elements deficiencies observed Zn 15.8%, Mg 11.1%, P 10.5% and Ca 6.4%, respectively. Conclusion: Considerable of unexpected deficiencies of the micronutrients was demonstrated in the focus population during the study. Global frequencies of deficiencies were hypozincemia, hypomagnesaemia, hypophosphatemia and hypocalcaemia, respectively. Sex distribution of electrolyte deficiencies noticed in Zn, Mg, P and Ca, individually. Moreover, the obvious some electrolyte disturbances in elderly should be considered as a health problem. Pre-operatively determination of unexpected electrolytes routinely may provide safety of surgery in our country.